Accurate income measurement for the assessment of public policies: Final report - Holly Sutherland; André Decoster; Manos Matsaganis; Panos Tsakloglou (University of Essex, Institute for Social and Economic Research (ISER), 2009)
[Note:] This paper is an adapted version of the substantive part of the Final Report to the European Commission of the project 'Accurate Income Measurement for the Assessment of Public Policies (AIM-AP)', under Priority 7 'Citizens and Governance in a Knowledge-based Society' of Framework Programme 6 [Project no. 028412].
Keywords: 330; Einkommensverteilung; Messung; Armut; Sozialpolitik; EU-Staaten